THE TRIGGER FOR FALLING LOYALTY ORIGINATING FROM PUBLIC RELATIONS AND CUSTOMER VALUES AND SATISFACTION - Bunga Aditi; Septa Diana Nabella; Arifin Djakasaputra; Dwi Septi Haryani; nasib nasib (International Journal of Artificial Intelligence Research, 2022)
Uncertainty requires every organization to continue to make improvements from all fields. The ability to respond quickly to existing changes is very expected. The main focus of this study is to analyze Public Relations and Customer Values on student satisfaction and student loyalty at the LP3M superior polytechnic. The population and sample in this study were active students in the academic year 2018-2019 totaling 117 students. Sampling techniques use nonprobability sampling using saturated samples. Data collection uses a Google From luminaire from sharing through the WhatsApp group. Where only 117 students were selected to be used as a population. However, those who responded to fill in this research questionnaire were only 98 respondents. Data analysis techniques use path analysis between the direct and indirect influence of the Public Relations and Customer Value variables on student loyalty through student satisfaction.The results showed that public relations had a significant effect on student satisfaction and student loyalty. Customer Value has a significant influence on satisfaction but has no significant influence on student loyalty. Then student satisfaction does not have a role in mediating between the Public Relations and Customer Values on student loyalty.